KARAKTERISTIK PETERNAK DAN STRATEGI PENGEMBANGAN TERNAK KERBAU GAYO SISTEM PERUWEREN - Rusli Rusli; Syahidin Syahidin (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2021)
The objective of the study was to determine the characteristics of breeders and the formulation of development strategies for the gayo buffalo in Linge District, Aceh Tengah Regency. This research method uses survey method, then analyzed using SWOT analysis (strength, weakness, opportunity and threat). Respondents were 54 Gayo buffalo breeders who were determined purposively. The results of this study were the characteristics of breeders in Linge District, namely education, livestock ownership and knowledge of breeders which were still very low. Meanwhile, for those who are still very productive and have high motivation in raising Gayo buffaloes in Linge District, Central Aceh Regency. Based on the results of the grand strategy, an aggressive strategy is obtained, namely utilizing empty land as a source of feed and processed feed as well as increasing livestock population and production through improved management of maintenance, feed and health by implementing the IB system.